QUILOMBOS IN THE DIASPORA AND THE ROLE OF ARCHEOLOGY: HISTORICAL STRUGGLES AND CHALLENGES, WRITTEN IN THE FIRST PERSON - da Silva Simoni, Rosinalda Olaséní Corrêa [UNESP] (Revista de Arqueologia da SAB, 2024)
The existence of the quilombo remnants is crossed by issues of race and racism, social, cultural, and historical vulnerabilities. Thus, I bring my personal history as a quilombola, in which you will perceive much of the discourses recorded during my field research in quilombos throughout America. I believe that the social role of any science and organization should be to promote reflections that provide social, political, economic, and behavioral changes, and it is no different with archaeology. We are far from an Afro-centric archaeology, but much closer than before. I believe that public archaeology brings in its premises this “message,” also called self-archaeology by Engmann and Irislane Moraes; a concept that, when applied, assists in understanding the processes of archaeological research and especially in recognizing and exercising the social role of archaeology. Thus, in this article I show reflections built from my existence as a quilombola black woman and as an archaeologist researcher, making use of this perspective, crossed by the struggles and strategies I experience in academia and outside it. Based on epistemological researchers concerned with understanding the social role of the human sciences, among them archaeology, such as Moraes, Kabengele Munanga, Abdias do Nascimento, Lélia Gonzales, Milton Santos, and many others.
LOS QUILOMBOS EN LA DIÁSPORA Y EL PAPEL DE LA ARQUEOLOGÍA: LUCHAS Y DESAFÍOS HISTÓRICOS, UN ESCRITO EN PRIMERA PERSONA
OS QUILOMBOS NA DIÁSPORA E O PAPEL DA ARQUEOLOGIA: LUTAS HISTÓRICAS E DESAFIOS, UMA ESCRITA NA PRIMEIRA PESSOA
Keywords: diaspora; quilombo; self-archaeology